Analisis Hukum Terhadap Pelaku Tindak Pidana Kepemilikan Narkotika (Studi Kasus Kota Makassar) - Rahmah, Andi; Pabbu, Amiruddin (Alauddin Law Development Journal, 2022)
This study aims to find out how the application of material criminal law in cases of narcotics possession crimes and to find out what the judges consider in making decisions against perpetrators of narcotics possession crimes. The research method used is normative legal research with a research approach that includes a statutory approach and a conceptual approach. Technique Analysis of the data was analyzed qualitatively, then from the results of the analysis will be poured descriptively. The application of the Material Criminal Law by the Judge to the Crime of Possession of Narcotics Category I in the Decision on Case Number 669/Pid.Sus/2021/PN.Mks has been correct. The Public Prosecutor used alternative charges, namely: Article 114 Paragraph (1) of the Law. RI. No. 35 of 2009 concerning Narcotics Jo Article 132 (1) of the Law. RI. No. 35 of 2009 concerning Narcotics, or Article 112 Paragraph (1) of the Law. RI. 35 of 2009 concerning Narcotics. Among the elements of the two Articles charged by the Public Prosecutor. Where the actions and the elements of the Article match each other. The judge’s legal consideration of the criminal act of Narcotics Ownership Category I is not a plant in imposing a sentence, it is appropriate because the Judge in case Number 669/Pid.Sus/2021/PN.Mks imposed a sentence based on witness testimony, defendant’s statement, and documentary evidence according to Article 184 KUHAP is legal evidence. Furthermore, the evidence supports the facts revealed in the trial which convinced the judge that the criminal act of Possession of Narcotics Category I was not a plant that actually occurred and that the defendant was guilty of committing it.